Global Diffusion of Protest. Riding the Protest Wave in the Neoliberal Crisis - della Porta, Donatella (Amsterdam University Press, 2017)
Recent years have seen a new development in the growth and spread of popular protest: protests that began as local, homogeneous events-such as Occupy Wall Street or the protests of the Arab Spring-quickly left their original locations and local specificity behind and became global. This book looks at the development of this wave of protests, with an eye on protests against austerity and neoliberal economic policies, and offers a global view, covering events in Turkey, Brazil, Venezuela, South Africa, Bosnia, Bulgaria, Ukraine, and other locations.